Graham Harvey, Animism: Respecting the Living World - Wallis, Robert J (Pomegranate, 2007)
Graham Harvey, Animism: Respecting the Living World (New York: Columbia University Press, 2005), 262 pp., 69.50 (cloth), 28.50 (paperback).